Faktor-faktor yang mempengaruhi tingkat kepatuhan wajib pajak orang pribadi pelaku e-commerce di Kota Labuan Bajo - Miftahul Jannah; Norman Duma Sitinjak (University of Merdeka Malang, 2023)
Taxes are a definite source of contributing funds to the state. This study aims to analyze the factors that influence taxpayer compliance, namely taxpayer awareness, tax sanctions, and understanding of taxation. The population used in this study is individual taxpayers who are e-commerce actors in Labuan Bajo City. The sampling technique uses random sampling, the type of data used is primary data sourced from distributing online questionnaires. The questionnaire given to 40 respondents used a Likert scale of 1 to 5. The criteria in this study were e-commerce taxpayers who made sales through the Market Place Shopee application who are domiciled in Labuan Bajo City and individual taxpayers who do e-commerce the author's data sources in this study.The research analysis technique used is multiple linear regression. Based on the results of the analysis, it shows that taxpayer awareness affects taxpayer compliance, tax sanctions do not affect taxpayer compliance, and understanding of taxation affects taxpayer compliance